Reduced Graphene Oxide-Extracellular Matrix Scaffolds as a Multifunctional and Highly Biocompatible Nanocomposite for Wound Healing: Insights into Characterization and Electroconductive Potential - Javier Cifuentes; Carolina Muñoz-Camargo; Juan C. Cruz (Nanomaterials, 2022)
The development of novel regenerative technologies based on the implementation of natural extracellular matrix (ECM), or individual components of ECM combined with multifunctional nanomaterials such as graphene oxide and reduced graphene oxide, has demonstrated remarkable results in wound healing and tissue engineering. However, the synthesis of these nanocomposites involves great challenges related to maintaining the biocompatibility with a simultaneous improvement in their functionalities. Based on that, in this research we developed novel nanoengineered ECM-scaffolds formed by mixing small intestinal submucosa (SIS) with graphene oxide (GO)/reduced graphene oxide (rGO) to improve electrical conductivity while maintaining remarkable biocompatibility. For this, decellularized SIS was combined with GO to form the scaffold precursor for subsequent lyophilization, chemically crosslinking and in situ reduction. The obtained GO and rGO were characterized via Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), X-ray diffraction (XRD), electrical conductivity testing and atomic force microscopy (AFM). The results confirm the suitable synthesis of GO, the effective reduction to rGO and the significant increase in the electrical conductivity (more than four orders of magnitude higher than bare GO). In addition, the graphene oxide/reduced graphene oxide-SIS scaffolds were characterized via Raman spectroscopy, FTIR, TGA, SEM, porosity assay (higher than 97.5% in all cases) and protein secondary structural analysis. Moreover, the biocompatibility of scaffolds was studied by standardized assays of hemolysis activity (less than 0.5%), platelet activation and deposition, and cell viability in Vero, HaCat and HFF-1 cells (higher than 90% for all evaluated cell lines on the different scaffolds). The obtained results confirm the remarkable biocompatibility, as supported by high hemocompatibility, low cytotoxicity and no negative impact on platelet activation and deposition. Finally, structural characteristics such as pore size and interconnectivity as well as superior cell attachment abilities also corroborated the potential of the developed nanoengineered ECM-scaffolds as a multifunctional nanoplatform for application in regenerative medicine and tissue engineering.